Regulation of SIRT1 in aging: Roles in mitochondrial function and biogenesis - Yuan, Y.; Cruzat, Vinicius; Newshome, Philip; Cheng, J.; Chen, Younan; Lu, Y. (2016)
© 2016 Elsevier Ireland Ltd. Aging is a degenerative process associated with cumulative damage, which leads to cellular dysfunction, tissue failure, and disorders of body function. Silent information regulator-1, also known as sirtuin 1 (SIRT1), has been reported to be involved in the regulation of various important biological processes, including inflammation, mitochondrial biogenesis, as well as cell senescence and consequent aging. The level of SIRT1 is decreased in both transcriptional and postranscriptional conditions during aging, accompanied by attenuated mitochondrial biogenesis, an important component of aging-related diseases. Over the last decade, extensive studies have demonstrated that SIRT1 can activate several transcriptional factors, such as peroxisome proliferator activated receptor γ co-activator 1α (PGC-1α) and hypoxia-inducible factor 1α (HIF-1α) resulting in ameliorated mitochondria biogenesis and extended life span. In this review, we focus on the molecular regulation of SIRT1 and its role in mitochondrial biogenesis during in the context of aging and aging-related diseases.